2016
DOI: 10.1080/10826068.2015.1135446
|View full text |Cite
|
Sign up to set email alerts
|

Isopropanol biodegradation by immobilized Paracoccus denitrificans in a three-phase fluidized bed reactor

Abstract: A three-phase bed bioreactor including a mix of immobilized microbes was used to degrade isopropanol (IPA). The immobilization method was studied and cells immobilized with calcium alginate, polyvinyl alcohol, activated carbon, and SiO were demonstrated to be the best immobilization method for the degradation of 90% of 2 g/L IPA in just 4 days, 1 day earlier than with free cells. Acetone was monitored as an indicator of microbial IPA utilization as the major intermediate of aerobic IPA biodegradation. The bior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Bacterial cells were entrapped in gellan gum following an earlier described method by Ahmed et al [ 24 , 51 ]. A culture was grown on a large-scale to obtain enough cells of the strain to be immobilized.…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial cells were entrapped in gellan gum following an earlier described method by Ahmed et al [ 24 , 51 ]. A culture was grown on a large-scale to obtain enough cells of the strain to be immobilized.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from the already mentioned micropollutants, isopropanol compounds are another prevalent toxic component of wastewater that has been widely disposed of by various cosmetic, rubber, etc. industries into watersources. , A study on the separation of isopropanol from aqueous solution was reported using liquid–liquid extraction with the help of two HDESs, namely, 1-decanol:methlytrioctylammonim chloride (2:1) and 1-hexanol:methyltrioctylammonium chloride (2:1) . The distribution coefficient and separation factor for isopropyl alcohol extraction were found to be in the ranges of 1.38–4.13 and 2.50–23.02, respectively, which indicated that the two HDESs were effective at removing isopropyl alcohol from wastewater.…”
Section: Applications Of Hdessmentioning
confidence: 99%